Conservative pharmacotherapy vs. staged percutaneous coronary intervention for non-culprit vessels in patients with ST-segment elevation myocardial infarction - Zhao, Bo (Exp Ther Med, 2016)
The present study aimed to compare the effect of conservative pharmacotherapy (CP) and staged percutaneous coronary intervention (SPCI) on significant non-culprit vessels in patients with ST-segment elevation myocardial infarction (STEMI). A total of 266 male and 40 female patients were divided into two groups following their first successful PCI treatment: i) Patients in the complete revascularization (CR) group undergoing SPCI; and ii) patients in the CP group undergoing CP. Follow-up data were collected at 180 or 360 days after surgery to compare the rates of major adverse cardiovascular events (MACE), recurrent myocardial infarction, recurrent angina pectoris and MACE-free survival rates between the two groups. The rate of MACE in the CP group was higher compared with that in the CR group at the 360-day follow-up (6.1 vs. 12.7%; P=0.05), and the same was reflected in the rate of recurrent myocardial infarction (10.1 vs. 4.1%; P=0.04). The rate of recurrent angina pectoris in the CP group was significantly higher compared with that in CR group at the 180-day (13.9 vs. 5.4%; P=0.012) and 360-day follow-up (18.4 vs. 8.1%; P=0.009). The MACE-free survival rate of patients was significantly higher in the CR group compared with that in the CP group at the 360-day follow-up (93.9% vs. 87.3%, P<0.05). In conclusion, the SPCI of non-culprit vessels in patients with STEMI is associated with better clinical outcomes than CP.